2013
DOI: 10.1111/pce.12220
|View full text |Cite
|
Sign up to set email alerts
|

Volatiles produced by soil‐borne endophytic bacteria increase plant pathogen resistance and affect tritrophic interactions

Abstract: Volatile organic compounds (VOCs) released by soil microorganisms influence plant growth and pathogen resistance. Yet, very little is known about their influence on herbivores and higher trophic levels. We studied the origin and role of a major bacterial VOC, 2,3-butanediol (2,3-BD), on plant growth, pathogen and herbivore resistance, and the attraction of natural enemies in maize. One of the major contributors to 2,3-BD in the headspace of soil-grown maize seedlings was identified as Enterobacter aerogenes, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(119 citation statements)
references
References 45 publications
3
107
0
2
Order By: Relevance
“…Enterobacter cloacae and Enterobacter aerogenes strains have been reported to control Fusarium oxysporum f. sp. spinaciae in spinach (Tsuda et al, 2001) and Setosphaeria turcica, the Northern corn leaf blight fungus, in maize (D'Alessandro et al, 2014). Biological control action of E. cloacae has also been reported by Roberts et al (1994).…”
Section: Discussionmentioning
confidence: 96%
“…Enterobacter cloacae and Enterobacter aerogenes strains have been reported to control Fusarium oxysporum f. sp. spinaciae in spinach (Tsuda et al, 2001) and Setosphaeria turcica, the Northern corn leaf blight fungus, in maize (D'Alessandro et al, 2014). Biological control action of E. cloacae has also been reported by Roberts et al (1994).…”
Section: Discussionmentioning
confidence: 96%
“…In animals and plants, BVCs function as elicitors and suppressors of immune responses respectively (Hsieh et al 2007;Rudrappa et al 2010). A test of several 2,3-butanediol stereoisomers indicated that only (2R,3R)-2,3-butanediol promoted plant growth and induced resistance/tolerance (Ryu et al 2004a, b;Han et al 2006;Cho et al 2008;D'Alessandro et al 2014). Intriguingly some insects also utilize acetoin and 2,3-butanediol as pheromones and kairomones (Buttery and Ling 1984;Nout and Bartelt 1998;Moore and Moore 1999;Moore et al 2002;Robacker and Lauzon 2002;Rochat et al 2002;Bengtsson et al 2009).…”
Section: New Roles For Acetoin and 23-butanediolmentioning
confidence: 98%
“…For example, Actinobacteria are well-known for antibiotic production and among most commonly encountered members of endophytic bacterial communities (Rosenblueth and Martínez-Romero, 2006) The production of secondary metabolites produced by plant-associated Actinobacteria are currently understudied (Brader et al, 2014). Some microbes can also lessen the amount of volatile organic compounds emitted that are used by herbivores and parasites to orient toward host plants (e.g., the green roof vegetation) (D'Aleessandro et al, 2014).…”
Section: Hypothesis 2: Microbial Associations Increases Plant Protectmentioning
confidence: 99%